VD_FINDINFO HC / 2014 / 870 vom 31. Oktober 2014 - VD Tribunal cantonal (2014)
AUGMENTATIONEN GÉNÉRAL, BAIL À LOYER, FICTION DE LA NOTIFICATION, FARDEAU DE LA PREUVE | 269d al. 1 CO, 316 al. 3 CPC (CH)